2020
DOI: 10.1021/acs.jafc.0c04678
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota: A Key Factor in the Host Health Effects Induced by Pesticide Exposure?

Abstract: In the past few decades, a large number of pesticides have been widely used for plant protection. Pesticides may enter non-target organisms through multiple ways and bring potential health risks. There is a dense and diverse microbial community in the intestines of mammals, which is called the gut microbiota. The gut microbiota and its metabolites play vital roles in maintaining the health of the host. Interestingly, many studies have shown that exposure to multiple pesticides could affect the gut microbiota o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 161 publications
0
27
0
Order By: Relevance
“…Atrazine, another widely used pesticide, is metabolized by rare gut bacteria Serratiamarcescens and Pseudomonas protegens , causing functional and inherited changes in the gut microbiota ( Wang et al., 2020 ). Thus, from the perspective of Meng et al., the gut microbiota is a key factor in the host health effects induced by pesticides ( Meng et al., 2020 ). Similarly, Chiu et al.…”
Section: The Interaction Of Gut Microbiota and Environmental Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrazine, another widely used pesticide, is metabolized by rare gut bacteria Serratiamarcescens and Pseudomonas protegens , causing functional and inherited changes in the gut microbiota ( Wang et al., 2020 ). Thus, from the perspective of Meng et al., the gut microbiota is a key factor in the host health effects induced by pesticides ( Meng et al., 2020 ). Similarly, Chiu et al.…”
Section: The Interaction Of Gut Microbiota and Environmental Hazardsmentioning
confidence: 99%
“…Atrazine, another widely used pesticide, is metabolized by rare gut bacteria Serratiamarcescens and Pseudomonas protegens, causing functional and inherited changes in the gut microbiota (Wang et al, 2020). Thus, from the perspective of Meng et al, the gut microbiota is a key factor in the host health effects induced by pesticides (Meng et al, 2020). Similarly, Chiu et al reviewed the impact of environmental chemicals on gut microbiota and suggested that pesticide exploration contributes to alterations in the composition, gene expression, function, and health effects in the host, including metabolism, immunity, and neurological function (Chiu et al, 2020).…”
Section: Chemical Factorsmentioning
confidence: 99%
“…The emerging exploration of the association between pesticides and the host's gut microbiota has completely changed the traditional understanding of pesticide-induced health effects of the host [36,37]. Several studies have proved the close association between gut microbiota and MetS [40][41][42].…”
Section: Low-dose Chi Disrupted Gut Microbiota Of Micementioning
confidence: 99%
“…Furthermore, the microbiota induced the in ammation of adipose tissue and increased the expression levels of genes responsible for fatty acid uptake in an FXR-dependent manner [34]. In particular, several studies have reported that pesticide exposure can disrupt the gut microbiota of the host [36,37]. Among them, few studies have suggested that the gut microbiota plays an important role in the pesticides' effects on host health [4,38].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, a large number of pesticides have been widely used for plant protection. Pesticides may enter non-target organisms through multiple ways and bring potential health risks ( Meng et al, 2020 ). Generally, the dysbiosis of gut microbiota often occurs simultaneously with the metabolic disorder of host.…”
Section: Introductionmentioning
confidence: 99%